2021
DOI: 10.1111/1756-185x.14130
|View full text |Cite
|
Sign up to set email alerts
|

A multicenter longitudinal study of the prevalence and mortality rate of systemic lupus erythematosus patients in Oman: Oman Lupus Study

Abstract: Aim This study is a longitudinal multicenter study which aims to find the prevalence, the demographic data, survival and mortality rates of patients with systemic lupus erythematosus (SLE) in Oman. Method All Omani patients, pediatrics and adults diagnosed with SLE, who fulfill either the 1997 American College of Rheumatology or Systemic Lupus International Collaborating Clinics classifications criteria for SLE were included from January 2006 till February 2020. Results In total 1160 patients were included in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…The case finding methodology and SLE ascertainment in all included cohorts is described in Supplementary Materials Table S1. All but three study locations included only SLE patients who fulfilled four or more of the American College of Rheumatology SLE classification criteria [8][9][10][11].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The case finding methodology and SLE ascertainment in all included cohorts is described in Supplementary Materials Table S1. All but three study locations included only SLE patients who fulfilled four or more of the American College of Rheumatology SLE classification criteria [8][9][10][11].…”
Section: Resultsmentioning
confidence: 99%
“…Five and ten-year survival differed in incident cohorts with patient inclusion before and after 1990 (five-year survival 80% versus 92% and ten-year survival 63% versus 88%) [10,[12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. For all studies with patient inclusion starting after 1990, the five-year survival was 90% or more, except for Barbados and Wisconsin [9,11,14,20,23,27,29]. In studies on total SLE cohorts, the SMR ranges from 1.9 to 4.6 [9,19,20,26,27,[30][31][32].…”
Section: Standardized Mortality Rate and Survivalmentioning
confidence: 99%
“…8 The other study was a large study of 1160 SLE patients conducted in Oman, which estimated the prevalence to be 38.8 per 100,000 population. 9 The considerable variation in prevalence in the three studies is likely due to differences in the methodological approaches. More data on the prevalence of SLE in the GCC region is needed.…”
Section: Incidence and Prevalence Of Sle In The Uaementioning
confidence: 99%
“…In the Arabian Peninsula region, several studies have been conducted to investigate the magnitude of the SLE and LN in their populations. [2][3][4][5][6][7][8][9] Most of the studies are very old, reporting cases from the 1990s and early 2000s. Additionally, some of these studies did not include clear clinical standards for diagnosing and characterizing LN.…”
Section: Introductionmentioning
confidence: 99%
“…20 In O'Neal et al's 21 study, they indicated that AF is more prevalent in Blacks than Whites (White being the main ethnic group in Europe and the USA). Also, Al-adhoubi et al 22 reported that the incidence and prevalence of SLE may be attributed to geographic differences. Therefore, SLE may be a risk factor for AF development and the results may vary with geographic distribution.…”
Section: Sle Tends To Increase Af Events and High Heterogeneity May B...mentioning
confidence: 99%